Geolektalne pułapki języka hiszpańskiego w praktyce przekładu pisemnego i ustnego - Kwiatkowska Faryś, Edyta; Wolarska-Sobocińska, Agata (Investigationes Linguisticae, 2019)
In the translatological perspective, the pluricentricity and big number of standard varietes of the Spanish language is a challenge, especially at the semantic and lexical level, as well as the phonetics and pragmatics are concerned. This study is an attempt to present the complexity and multidimensionality of the problem. On the basis of selected specific examples, the paper shows how the ability to recognize and distinguish specific geolects equips a translator/interpreter of Spanish with the tools of effective communication and a culture oriented interpretation.